Synthesis of guaian sesquiterpene γ-lactones from hanphilline - Merkhatuly, N.; Abeuova, S.B.; Omarova, A.T.; Balmagambetova, L.T. (KSU publ., 2014)
Synthetic methods of guaianolides on the basis of germacranolide E,E-hanphilline were presented in this article. Hanphilline is a characteristic component of the Noble Yarrow (Achillea nobilis L.), which is widespread in Central Kazakhstan. Synthesis of obtained guaianolides were carried out with stereocontrolled 1,5-cyclization of E,E-germaсranolide (+)-hanphilline. The one-step stereospecific syntheses of guaianolides on the basis of available germacradienolide E,E-hanphilline were developed and carried out. The mechanism of 1,5-carbocyclization was considered. Scheme of biogenetic interdependence of guaianolides in Achillea nobilis L. was offered. It allowed a deeper understanding of a very complex process of biosynthesis of sesquiterpene lactones in the plant body.
Keywords: sesquiterpene lactones; guaianolides; germacranolides; stereocontrolled synthesis; hanphilline; carbocyclization; biogenetic interdependence; quantum-chemical calculations